Cortical microstructural changes associated with treated aphasia recovery. Issue 9 (18th August 2021) - Chang, Allen J.; Wilmskoetter, Janina; Fridriksson, Julius; McKinnon, Emilie T.; Johnson, Lorelei P.; Basilakos, Alexandra; Jensen, Jens H.; Rorden, Chris; Bonilha, Leonardo
Abstract: Objectives: To investigate the hypothesis that language recovery in post‐stroke aphasia is associated with structural brain changes. Methods: We evaluated whether treatment‐induced improvement in naming is associated with reorganization of tissue microstructure within residual cortical regions. To this end, we performed a retrospective longitudinal treatment study using comprehensive language‐linguistic assessments and diffusion MRI sequences optimized for the assessment of complex microstructure (diffusional kurtosis imaging) to evaluate the relationship between language treatment response and cortical changes in 26 individuals with chronic stroke‐induced aphasia. We employed elastic net statistical models controlling for baseline factors including age, sex, and time since the stroke, as well as lesion volume. Results: We observed that improved naming accuracy (Philadelphia Naming Test) was statistically associated with increased post‐treatment microstructural integrity in the left posterior superior temporal gyrus. Moreover, increase in microstructural integrity in the left middle temporal gyrus and left inferior temporal gyrus was specifically associated with a decrease in semantic paraphasias. This longitudinal relationship between brain tissue integrity and language improvement was not observed in other non‐language related brain regions. Interpretation: Our findings provide evidence that structural brain changes in the preserved left hemisphere regions are associated with treatment‐induced language recovery in aphasia and are part of the mechanisms supporting language and brain injury recovery.